Evaluation of genetic diversity of Estahban region fig genotypes based on morphological traits and SCoT molecular markers - Elaheh Ranjbaran; Mehdi Rahimi; Maryam Abdolinasab; Hamid Zare; Mojtaba Kordrostami (مجله بیوتکنولوژی کشاورزی)
ObjectiveFig (Ficus carica) is a deciduous tree that is grown in arid and semi-arid regions. Figs, as an important crop, have undergone genetic erosion in recent decades due to living and non-living stresses. The aim of this study was to determine the genetic diversity of genotypes in Estahban using morphological traits and Start Codon Targeted (SCoT) molecular markers.  Materials and methodsIn this study, 16 fig genotypes were evaluated in a completely randomized design with three replications based on their morphological traits. Also, their genomic DNA was extracted from leaves and the genotypic diversity of genotypes based on 10 SCoT primers was examined.ResultsVariance analysis showed a significant difference between traits, and cluster analysis based on morphological traits placed the genotypes in five groups. Eight primers amplified a total of 50 polymorphic bands, and SCoT12 and SCoT11 produced the most bands with 13 and 9 polymorphic bands, respectively. The polymorphic information content (PIC) for the SCoT primers varied between 0.3423 and 0.3791 with an average of 0.3595. Cluster analysis by UPGMA and Gower similarity criterion based on SCoT data, 16 fig genotypes were placed in four groups. The grouping based on the Bayesian method placed the genotypes in nine groups, although the genotypes were not differentiated and were a mixture of all nine groups.ConclusionsThe results indicate that the use of SCoT marker has a high advantage and plays an important role in the differentiation of fig genotypes. In general, it can be said that SCoT molecular markers and morphological traits have shown high diversity among genotypes. In general, the results obtained from this study indicate the existence of high genetic diversity in the germplasm of Estahban fig cultivars, which can be used in breeding programs by protecting this rich germplasm source.